Establishing an independent mobile health programme for chronic disease self-management support in Bolivia - John D Piette; John D Piette; Helen eValverde; Nicolle eMarinec; Nicolle eMarinec; Rachel eJantz; Kevin eKamis; Carlos eLazo de la Vega; Timothy eWooley; Bismarck ePinto (Frontiers Media S.A., 2014)
Background: Mobile health (m-health) work in low and middle-income countries (LMICs) mainly consists of pilot programmes with an unclear path to scaling and dissemination. We describe the deployment and testing of an m-health platform for non-communicable disease (NCD) self-management support in Bolivia. Methods: 364 primary care patients in La Paz with diabetes or hypertension completed surveys about their use of mobile phones, health and access to care. 165 of those patients then participated in a 12-week demonstration of automated telephone monitoring and self-management support. Weekly Interactive Voice Response (IVR) calls were made from a platform established at a university in La Paz, under the direction of the regional health ministry. Results: 37% of survey respondents spoke indigenous languages at home, and 38% had six or fewer years of education. 82% had a mobile phone; half (45%) used text messaging with a standard phone, and 9% had a smartphone. Smartphones were least common among patients who were older, spoke indigenous languages, or had less education. IVR programme participants completed 1007 self-management support calls, with an overall response rate of 51%. IVR call completion was lower among older adults, but was not related to patients' ethnicity, health status or healthcare access. IVR health and self-care reports were consistent with information reported during baseline interviews. Patients' likelihood of reporting excellent, very good, or good health (versus fair or poor health) via IVR increased during programme participation, and was associated with better medication adherence. Patients completing follow-up interviews were satisfied with the programme, with 19/20 (95%) reporting that they would recommend it to a friend. Conclusions: By collaborating with LMICs, m-health programmes can be transferred from higher-resource centres to LMICs and implemented in ways that improve access to self-management support among people with NCDs.